2017
DOI: 10.1515/ijme-2017-0019
|View full text |Cite
|
Sign up to set email alerts
|

Culture-Based Rejection of Taboo-Infringing Imports

Abstract: This empirical study analyzes the cultural basis of the United States market response to imported Spanish products that seem to violate strongly-held cultural taboos. Survey responses were obtained from students in two contrasting majors, Art and Business, in two distinct cities and universities, i.e. Little Rock at the University of Arkansas, and Dominguez Hills at California State University. The study focused on a baby doll marketed to piggy-back on the new movement towards breastfeeding babies. Although ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Differing cultural values and beliefs have also been found to lead to differing business behavior and performance [Brice and Jones, 2013;Brice, 2012]. On a smaller-scale, populations within the same country have been found to enthusiastically accept or adamantly reject imported products that seemed to violate cultural norms for one group but fit the cultural norms for another [Brice, et al, 2017]. There seemed to be no basis for compromise (with the product or its marketing) with these differing cultural groups as they proceed from differing cultural values, beliefs as well as differing reality platforms.…”
Section: Fig 9: Conflicts Involving Four Realitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Differing cultural values and beliefs have also been found to lead to differing business behavior and performance [Brice and Jones, 2013;Brice, 2012]. On a smaller-scale, populations within the same country have been found to enthusiastically accept or adamantly reject imported products that seemed to violate cultural norms for one group but fit the cultural norms for another [Brice, et al, 2017]. There seemed to be no basis for compromise (with the product or its marketing) with these differing cultural groups as they proceed from differing cultural values, beliefs as well as differing reality platforms.…”
Section: Fig 9: Conflicts Involving Four Realitiesmentioning
confidence: 99%
“…The belief patterns discussed here are as fundamental as Hofstede's (2001) cultural dimensions. Research concerning culture-based taboos has shown how strong and fundamental these types of conflicting attitudes can be; as well as how they are linked to specific groups in society (Brice, et al, 2017). Furthermore, in the context of overwhelming social polarization, especially in Western societies, it is argued here that we must negotiate across these basic realities when entering a dialogue and facing differences; recognizing the games that are played among participants to attain goals defined in terms of their diverse realities.…”
Section: Introductionmentioning
confidence: 97%